REPRISE 3b Study in Enrollment Phase - Vinall, Maria (MD Conference Express, 2015)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common inherited kidney disease in adults and is the fourth-leading cause of end-stage renal disease. The Efficacy and Safety of Tolvaptan in Subjects With Chronic Kidney Disease Between Late Stage 2 to Early Stage 4 Due to Autosomal Dominant Polycystic Kidney Disease [REPRISE 3b; NCT02160145] study's objective is to compare the efficacy of tolvaptan, a selective arginine vasopressin V2 receptor antagonist, with placebo in adults with ADPKD. Results are discussed in this article.